The pathogenic factor of ZC4H2-associated rare disorder is a postsynaptic regulator for synaptic activity and cognitive function - Li Pear Wan; Yuwei Li; Shuhua Zhao; Shiping Zhao; Ning-Ning Song; Kai-Ming Yuan; Cuiping Yang; Yu-Qiang Ding; Bingyu Mao; Nengyin Sheng; Wucheng Tao; Pengcheng Ma (Proceedings of the National Academy of Sciences, 2025)
The maintenance of excitatory synaptic activity is crucial for cognitive function and genetic mutations are responsible for the pathogenesis of related brain disorders. However, the roles of these pathogenic factors in synaptic dysregulation and cognitive malfunction are still poorly understood. In this study, a conditional knockout mouse model lacking ZC4H2 —an X-linked gene implicated in ZC4H2-associated rare disorder (ZARD) —in forebrain excitatory neurons is generated and these mice exhibit cognitive malfunction, recapitulating the intellectual disability manifestation of ZARD. Mechanistically, ZC4H2 harbors a protein interaction network with key excitatory synaptic regulators and ZC4H2 interacts directly with AMPA receptors (AMPARs) and regulates their ubiquitination at the postsynaptic sites, thereby maintaining AMPARs protein stability and synaptic expression. ZC4H2 deficiency specifically and aberrantly increases AMPAR-mediated excitatory synaptic transmission and impairs synaptic plasticity of long-term potentiation. More importantly, pharmacological treatment with perampanel, an AMPAR-specific antagonist, successfully restores the excitatory synaptic activity and cognitive function of ZC4H2-deficient mice. Together, we establish that ZC4H2 is a postsynaptic regulator for AMPARs and excitatory synaptic activity and highlight that the dysregulation of these biological processes is a crucial etiology underlying ZARD-associated intellectual disability.